ARFI shear-wave elastography with simulation of acute urinary tract obstruction in an ex vivo porcine kidney model - Muttray, Jens (Diagn Interv Radiol, 2018)
PURPOSE: We aimed to evaluate if acoustic radiation force impulse (ARFI) shear-wave elastography (SWE) can detect change of parenchymal stiffness in an ex vivo porcine kidney model of acute urinary tract obstruction. METHODS: A total of 20 heparinized pig kidneys were investigated at 10 intrapelvic hydrostatic pressure steps (0–90 mmHg). SWE (ARFI; Virtual Touch(™) IQ, Siemens) measurements were taken at three different measuring regions and in two measuring sequences using a linear ultrasonography probe (9L4, Siemens). Median values of 10 shear-wave speed (SWS) measurements were calculated for each pressure step. Logarithmic transformed median SWS values were analyzed in a linear mixed model. RESULTS: SWS increased significantly with increasing intrapelvic pressure. Median SWS for all kidneys in both measuring sequences and all measuring regions was 1.47 m/s (interquartile range [IQR], 0.38 m/s) at 0 mmHg, 1.94 m/s (IQR, 0.42 m/s) at 30 mmHg, 2.07 m/s (IQR, 0.43 m/s) at 60 mmHg, 2.24 m/s (IQR, 0.49 m/s) at 90 mmHg. The correlation between pelvic pressure increase and median SWS values for the central parenchyma was significantly higher compared with the peripheral parenchyma. CONCLUSION: Acutely increased renal pelvic pressure correlates with increasing SWS values in ARFI elastography in an ex vivo porcine kidney model.